462PUsefulness for prevention of postoperative cerebrovascular complications in patients with lung cancer using carotid ultrasonography. (24th November 2019) - Takeo, S; Shoji, F; Toyokawa, G; Yamazaki, K; Kozuma, Y
Abstract: Background: Stroke is a major cause of morbidity or mortality after lung surgery. CAS is useful for detecting carotid artery stenosis, which is one of the causes of stroke. To investigate the frequency of, and risk factors for, preoperative carotid artery stenosis and to determine whether ultrasonographic carotid artery screening (CAS) contributes to preventing postoperative stroke or cardiovascular comorbidities in lung cancer patients. Methods: This retrospective study included 1676 consecutive lung cancer patients underwent surgical resection. Results: Of the 1342 patients who underwent CAS, 173 (12.9%) had carotid artery stenosis. Significant associations with carotid artery stenosis were found for older patients (p < 0.0001), men (p < 0.0001), smoking history (p < 0.0001), history of stroke (p = 0.0037), cardiovascular diseases (p < 0.0001), hypertension (p = 0.0353), diabetes mellitus (p = 0.0037), and peripheral vascular diseases (p < 0.0001). Patients with the three or more independent risk factoqrs had a 7.91-fold higher prevalence of carotid artery stenosis (odds ratio 7.91, 95% confidence interval 1.91 to 32.79), than those with none of these factors. Propensity score matched analysis showed that incidences of both postoperative stroke and cardiovascular comorbidities were lower in patients who underwent CAS and received appropriate anticoagulant therapy than in those who did not (p = 0.0619 and 0.0319, respectively). Conclusions: Preoperative CAS is a simple and useful tool for detecting carotid artery stenosis. Administration of perioperative anticoagulant therapy to preoperative patients with lung cancer and carotid artery stenosis identified by CAS may prevent postoperative stroke and cardiovascular events. Legal entity responsible for the study: Thoracic Surgery, Clinical Research Institute, National Hospital Organization Kyushu Medical Center. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.